ECONOMIC AND SOCIAL INEQUALITY IN THE DIGITAL ERA: A LITERATURE REVIEW OF OPPORTUNITIES AND CHALLENGES - Loso Judijanto (Adisam Publisher, 2025)
Digital transformation has become a global trend that provides many conveniences and opportunities for society. However, several studies have shown that these changes can also widen economic and social disparities if not handled properly. This paper aims to review recent research on the potential and challenges of digital technology in dealing with inequality issues. The literature review shows that digital technologies have the ability to increase inclusion and access to resources, but also potentially pose risks of exclusion for vulnerable groups, bias in algorithms, and concentration of power by giant digital companies. Successfully harnessing the benefits of digital transformation to achieve socio-economic justice requires collaboration between the government, private sector and civil society in developing comprehensive policies and regulations. Only with a planned and sustained collective effort can digitalisation become a catalyst for a more just and inclusive society.